Nanostructures and catalytic atoms engineering of tellurium‐based materials and their roles in electrochemical energy conversion. Issue 1 (29th July 2022) - Li, Tiantian; Deng, Yuting; Rong, Xiao; He, Chao; Zhou, Mi; Tang, Yuanjiao; Zhou, Hongju; Cheng, Chong; Zhao, Changsheng
Abstract: With the dramatic developments of renewable and environmental‐friendly electrochemical energy conversion systems, there is an urgent need to fabricate durable and efficient electrocatalysts to address the limitation of high overpotentials exceeding thermodynamic requirements to facilitate practical applications. Recently, tellurium‐based nanomaterials (Te NMs) with unique chemical, electronic, and topological properties, including Te‐derived nanostructures and transition metal tellurides (TMTs), have emerged as one of the most promising electrocatalytic materials. In the absence of comprehensive and guiding reviews, this review comprehensively summarizes the main advances in designing emerging Te NMs for electrocatalysis. First, the engineering strategies and principles of Te NMs to enhance their electrocatalytic activity and stability from the nanostructures to the catalytic atoms are discussed in detail, especially on the chemical/physical/multiplex templating strategies, heteroatom doping, vacancy/defect engineering, phase engineering, and the corresponding mechanisms and structure‐performance correlations. Then, typical applications of Te NMs in electrocatalysis are also discussed in detail. Finally, the existing key issues and main challenges of Te NMs for electrocatalysis are highlighted, and the development trend of Te NMs as electrocatalysts is expounded. This review provides new concepts to guide future directions for developing Te NMs‐based electrocatalysts, thereby promoting their future wide applications in electrochemical energy systems. Abstract : Recent advances in tellurium‐based nanomaterials (Te NMs) for electrocatalytic applications have been summarized in this review. The design principles and modification strategies of Te NMs in structural engineering and catalytically active center design, such as chemical/physical/multiplex templating strategies, heteroatom doping, vacancy/defect engineering, and phase engineering, are discussed. The electrocatalytic applications, main challenges, and development directions of Te NMs are also summarized.